A new Octacnemidae (Ascidiacea) from the Mid-Atlantic Ridge - Monniot, Françoise (Zootaxa, 2011)
A new deep sea Octacnemidae (Ascidiacea, Phlebobranchia) was collected by IFREMER during the Hydrosnake cruise on the N.O. Nadir in July 1988 with the submersible Nautile. The site is located on the Mid-Atlantic ridge, in the Kane fracture zone at 2100m depth. The substratum consists of masses of fallen basalt blocks lying on black pebbles. A single specimen was attached to an easily breakable black stone with manganese particles. This ascidian represents the second specimen of the genus Myopegma Monniot & Monniot, 2003 previously known from the Pacific Ocean off New Calédonia.